Review Peraturan dan Kebijakan Pemerintah terhadap Pariwisata di Indonesia - Zulfatah Yasin (Prodi Ahwal Syakhsiyah, Fakultas Syariah, Institut PTIQ Jakarta, 2022)
This study aims to analyze tourism regulations and policies as the main sector of the economy using descriptive analysis methods, library research and comparisons of the two countries of Indonesia and Japan. This study uses a comparative study method between Indonesia and Japan. It was found that Indonesia has a